2010
DOI: 10.1093/intqhc/mzq031
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the measure of processes of care for adults: a measure of client-centred care

Abstract: MPOC-A has demonstrated good psychometric properties. As general satisfaction scores are notoriously poor indicators of the quality of care, this measure can help us understand the elements that contribute to overall judgements of satisfaction and provide a level of understanding that is important to improve service quality and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 33 publications
2
41
3
1
Order By: Relevance
“…In the past, satisfaction with care measures were often used to assess the quality of care. However, these tools tend to have high ceiling effects and do not provide a comprehensive picture of clients’ and clinicians’ experiences 7,8…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, satisfaction with care measures were often used to assess the quality of care. However, these tools tend to have high ceiling effects and do not provide a comprehensive picture of clients’ and clinicians’ experiences 7,8…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, we reported the validation of the adapted measure of processes of care (MPOC) from the perspectives of adult clients undergoing elective joint replacement 7. At the time of that study, the measure was the only available generic tool that allowed evaluation of the client- and family-centeredness of care in adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emberton and Black [25] and Polk et al [26] found that the distortions due to non-respondents in the results of postsurgery satisfaction surveys are negligible. Since the influence of nonparticipants could not be controlled and the net rate of return was 12.1% and 12.2%, respectively, potential response bias and its resulting limitations to the study results cannot be excluded [27]. Second, while the sample of patients from 43 hospitals does approximate the hospital structure of a region of Germany, the ability to generalize the results to other regions and countries still needs to be clarified [28].…”
Section: Limitationsmentioning
confidence: 99%
“…På grunn av de mange aktørene Habiliteringstjenester samarbeider med, vil det vaere behov for en bredere tilnaerming når vi skal søke brukernes vurdering. En voksen-utgave av MPOC-20 er utviklet (MPOC-A; (Bamm, Rosenbaum, & Stratford, 2010)), men fokuset for denne er i likhet med MPOC-20 relasjonen mellom familie og veiledningsaktør. Voksne med funksjonshemming bor ofte ikke i foreldrehjemmet, og det er ulikt i hvilken grad foreldre er involvert i behandlingsforløpet.…”
Section: Innledningunclassified